Quantitative methods for capturing processes and contexts in educational research - Malmberg, Lars-Erik (Revista Española de Pedagogía, 2018)
Open Access Technological and methodological advances enable new substantive research questions to be posed, and new study designs to be implemented, in educational research. In this paper I review emerging methods relevant for capturing learning and teaching processes over time —the sequences of learning events— which take place in multiple contexts. To do so, the concepts of nomothetic and ideographic research are traced through the use of Cattell’s (1952) cube, posing persons, variables and time as the three key dimensions for determining study-designs. For educational research, a fourth dimension —context— is important to consider given the nested structures (e.g. student-teacher dyads, peerrelations, student-groups, classrooms, teachers, and schools) learning and teaching occurs in. Several developments of quantitative methods enable researchers to a) establish quality of measurement (e.g. factor analysis, item response models), b) across sequences of time-points (e.g. autoregressive models), c) in complex multilevel structures (e.g. multilevel models, random effects models), also using estimators which are robust for small-n studies (e.g. Bayesian models). Educational researchers are encouraged to design studies fitting multilevel models for hierarchically and cross-classified data, and to think in terms of intraindividual learning processes.
Métodos cuantitativos para el registro de procesos y contextos en la investigación educativa
Los avances tecnológicos y metodológicos permiten formular nuevas preguntas de investigación fundamentales y aplicar nuevos diseños de estudios en la investigación educativa. Este artículo revisa los métodos emergentes empleados para el registro de los procesos de aprendizaje y enseñanza en el tiempo —las secuencias de eventos de aprendizaje— que tienen lugar en contextos múltiples. Para este fin, se emplean los conceptos de investigación nomotética e ideográfica utilizando el cubo de Cattell (1952), que identifica a las personas, las variables y el tiempo como las tres dimensiones clave para describir diseños de estudios. En la investigación educativa es importante tener en cuenta una cuarta dimensión —el contexto— dadas las estructuras anidadas (p. ej. díadas alumno- profesor, relaciones entre pares, grupos de alumnos, aulas, profesores y colegios) en las que se produce el aprendizaje y la enseñanza. Existen varios métodos cuantitativos que permiten a los investigadores: a) determinar la calidad de la medición (p. ej. el análisis de factores, los modelos de respuesta a ítems), b) en secuencias de puntos temporales (p. ej. modelos autorregresivos), c) en estructuras multinivel complejas (p. ej. modelos multinivel, modelos de efectos aleatorios), empleando también estimadores sólidos en estudios de n pequeña (p. ej. modelos bayesianos). Se invita a los investigadores en educación a diseñar estudios apropiados para modelos multinivel con datos clasificados jerárquicamente o con clasificación cruzada, y a pensar en términos de procesos de aprendizaje intraindividuales.
Keywords: educational research; quantitative methods; statistical models; multilevel model; intensive longitudinal data; investigación educativa; métodos cuantitativos; modelos estadísticos; modelo multinivel; datos longitudinales intensivos; Revista Española de Pedagogía